2022
DOI: 10.1021/acs.estlett.2c00171
|View full text |Cite
|
Sign up to set email alerts
|

Biomagnification and Temporal Trends of New and Emerging Dechloranes and Related Transformation Products in Baltic Sea Biota

Abstract: To enhance knowledge of the environmental distribution and temporal trends of dechloranes and their transformation products (TPs) we performed suspect screening of Baltic Sea biota (eelpout, herring, harbor porpoise, guillemot and white-tailed sea eagle). Evaluation of new and “digitally frozen” gas chromatography/high-resolution mass spectrometry data revealed 31 compounds: five dechloranes (Dechlorane [Mirex], Dechlorane 602, Dechlorane 603, and syn -/ anti -Dech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The NORMAN collaborative trials demonstrated that LC-HRMS could only cover part of the chemical domain of organic contaminants and highlighted an urgent need for development of GC-HRMS workflows [9,10]. Screening studies may also focus on compounds that are best analysed with GC-HRMS, for example, addressing bioaccumulation in lipid-rich tissues [165] and volatile compounds in air [166,167]. The general considerations for optimised separation are similar to those for LC-based analyses (Sect.…”
Section: Choice Of Chromatographymentioning
confidence: 99%
“…The NORMAN collaborative trials demonstrated that LC-HRMS could only cover part of the chemical domain of organic contaminants and highlighted an urgent need for development of GC-HRMS workflows [9,10]. Screening studies may also focus on compounds that are best analysed with GC-HRMS, for example, addressing bioaccumulation in lipid-rich tissues [165] and volatile compounds in air [166,167]. The general considerations for optimised separation are similar to those for LC-based analyses (Sect.…”
Section: Choice Of Chromatographymentioning
confidence: 99%
“…The present work represents the first multihalogen mass balance investigation in municipal WWTP sludge and offers unique insights into the extracts/extraction procedures which yield high concentrations of unidentified EOX. This approach offers a complementary tool to other nontarget prioritization strategies, such as case-control, 72 time trends, 73 and biomagnification factors, 74 but is unique in that it identifies specific halogen class(es) and extraction technique(s), rather than a specific feature of a mass spectrum. However, despite showing considerable potential for widespread adoption and applications to a wider suite of matrices, there remains a scarcity of reference material necessary for standardization of halogen mass balance methods.…”
Section: Resultsmentioning
confidence: 99%
“…There is a paucity of data on the occurrence of lipophilic organofluorine, with the exception of a single report of high EOF in the blubber of a Greenland Killer whale, 20 and a more recent article predicting the environmental occurrence of mixed halogenated n-alkanes (including those containing fluorine). 71 72 time trends, 73 and biomagnification factors, 74 but is unique in that it identifies specific halogen class(es) and extraction technique(s), rather than a specific feature of a mass spectrum. However, despite showing considerable potential for widespread adoption and applications to a wider suite of matrices, there remains a scarcity of reference material necessary for standardization of halogen mass balance methods.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The present work represents the first multi-halogen mass balance investigation in municipal WWTP sludge, and offers unique insights into the extracts/extraction procedures which yield high concentrations of unidentified EOX. This prioritization offers a complementary tool to other non-target prioritization approaches, such as case-control, 64 time trends, 65 and biomagnification factors, 66 but is unique in that it identifies specific halogen class(es) and extraction technique(s), rather than a specific feature of a mass spectrum. While showing considerable potential for widespread adoption and applications to a wider suite of matrices, this approach has several limitations and areas for further development, which should be addressed in future studies.…”
Section: Perspectives and Limitations On The Use Of Ohc Mass Balance ...mentioning
confidence: 99%